2018
DOI: 10.1093/toxsci/kfy002
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of O-GlcNAc Levels in the Liver Impacts Acetaminophen-Induced Liver Injury by Affecting Protein Adduct Formation and Glutathione Synthesis

Abstract: Overdose of acetaminophen (APAP) results in acute liver failure. We have investigated the role of a posttranslational modification of proteins called O-GlcNAcylation, where the O-GlcNAc transferase (OGT) adds and O-GlcNAcase (OGA) removes a single β-D-N-acetylglucosamine (O-GlcNAc) moiety, in the pathogenesis of APAP-induced liver injury. Hepatocyte-specific OGT knockout mice (OGT KO), which have reduced O-GlcNAcylation, and wild-type (WT) controls were treated with 300 mg/kg APAP and the development of injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 63 publications
4
17
1
Order By: Relevance
“…It seems that prolonged disruption of the balance between hepatocyte survival and death is a critical determinant for chronic liver disease but not in acute liver failure. A recent paper showed that systemic administration of the OGA inhibitor exacerbates acetaminophen-induced liver injury, and hepatic depletion of OGT with AAV protects the mice from such injury (41). The discrepancies between this study and our current study may result from the different methods used to manipulate O-GlcNAc signaling in the liver.…”
Section: Discussioncontrasting
confidence: 80%
“…It seems that prolonged disruption of the balance between hepatocyte survival and death is a critical determinant for chronic liver disease but not in acute liver failure. A recent paper showed that systemic administration of the OGA inhibitor exacerbates acetaminophen-induced liver injury, and hepatic depletion of OGT with AAV protects the mice from such injury (41). The discrepancies between this study and our current study may result from the different methods used to manipulate O-GlcNAc signaling in the liver.…”
Section: Discussioncontrasting
confidence: 80%
“…(1) A recent report has indicated that hyper-O-GlcNAcylation promotes acetaminophen-induced liver injury, which is contrary to the expected beneficial effect of this posttranslational modification on autophagy, but may be explained by autophagy-independent effects on glutathione biosynthesis. (7) This finding together with the current study suggests that maintaining O-GlcNAcylation at an optimal level is required for hepatic homeostasis. (8) The varied functions of O-GlcNAcylation, which may differ depending on cellular levels, make it uncertain as to whether this pathway would be a viable therapeutic target to increase autophagy in disease states.…”
supporting
confidence: 74%
“…Autophagy limits mouse hepatic injury from galactosamine/lipopolysaccharide and acetaminophen through a variety of mechanisms including the downregulation of caspase activation and removal of protein adducts, respectively . A recent report has indicated that hyper‐O‐GlcNAcylation promotes acetaminophen‐induced liver injury, which is contrary to the expected beneficial effect of this posttranslational modification on autophagy, but may be explained by autophagy‐independent effects on glutathione biosynthesis . This finding together with the current study suggests that maintaining O‐GlcNAcylation at an optimal level is required for hepatic homeostasis .…”
supporting
confidence: 49%
“…Alternatively, it is possible that TMG and glucosamine are acting through different mechanisms, since glucosamine perturbs the HBP upstream of TMG. TMG was synthesized based on rational design and has been used extensively with the express purpose inhibiting OGA with minimal off‐target effects (de Queiroz, Madan, Chien, Dias, & Slawson, ; McGreal et al, ; Tan et al, ; Yuzwa et al, ; Zhang et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, glutathione present in the egg is a thiol‐reducing agent that reduces the protamine disulfide bonds in the first steps of sperm DNA decondensation (Caglar et al, ). Interestingly, induction of O ‐GlcNAcylation results in dysregulation of hepatic glutathione replenishment in a model of acetaminophen‐induced liver injury (McGreal et al, ). Thus, it is possible that meiotic maturation in the presence of TMG affects glutathione levels in the oocyte, which may have downstream consequences in the zygote on sperm head decondensation.…”
Section: Discussionmentioning
confidence: 99%